High sensitivity and reproducibility of in‐house ELISAs using different genotypes of Trypanosoma cruzi. (25th April 2019) - Caballero E., Zuleima; Correa, Ricardo; Nascimento, Marilda S.; Villarreal, Alcibiades; Llanes, Alejandro; Kesper, JR., Norival
Summary: The adequate choice of Trypanosoma cruzi strains as antigen source for the diagnosis of Chagas disease is still controversial due to differences in terms of accuracy reported between different diagnostic tests. In this study was determined if the genetic variability between different genotypes of T. cruzi (TcI, TcII and TcIV) affect the final diagnosis of Chagas disease. The sensitivity and specificity index of in‐house ELISA tests prepared with different T. cruzi strains were evaluated with chagasic and non‐chagasic control sera and using the TESA‐blot as a reference test. The results of this study revealed that the sensitivity index did not vary, with percentages of 100% for all strains in both tests. However, the specificity index for ELISA tests showed differences between 92% and 98%, but were reduced to 78%‐89% when Leishmania ‐positive sera were included. All ELISAs and TESA‐blot prepared with different antigens and the recombinant Wiener test were challenged in an endemic community for Chagas disease in Panama. Both ELISAs and TESA‐blot recognized the same positive sera, corroborating the sensitivity indexes (100%) found with the control sera. The TESA‐blot maintained the specificity index of 100% and did not display false positives. However, the recombinant Wiener test decreased its sensitivity to 81.25%.